Categorising hybrid material microfluidic devices - Carvell, Tom; Burgoyne, Paul; Fraser, Alasdair R.; Bridle, Helen (Frontiers in Lab on a Chip Technologies, 2024)
Microfluidic devices are useful tools for a wide range of biomedical, industrial, and environmental applications. Hybrid microfluidic devices utilising more than two materials are increasingly being used for their capacity to produce unique structures and perform novel functions. However, an analysis of publications across the field shows that whilst hybrid microfluidic devices have been reported, there remains no system of classifying hybrid devices which could help future researchers in optimising material selection. To resolve this issue, we propose a system of classifying hybrid microfluidic devices primarily as containing either hybrid structural, chemical, or electrical components. This is expanded upon and developed into a hierarchy, with combinations of different primary components categorised into secondary or tertiary hybrid device groupings. This classification approach is useful as it describes materials that can be combined to create novel hybrid microfluidic devices.